Dietary flavonoids and flavonoid-rich foods: validity and reproducibility of FFQ-derived intake estimates. Issue 18 (23rd December 2020) - Yue, Yiyang; Petimar, Joshua; Willett, Walter C; Smith-Warner, Stephanie A; Yuan, Changzheng; Rosato, Sinara; Sampson, Laura; Rosner, Bernard; Cassidy, Aedin; Rimm, Eric B; Ivey, Kerry L
Abstract: Objective: To evaluate the validity and reproducibility of a 152-item semi-quantitative FFQ (SFFQ) for estimating flavonoid intakes. Design: Over a 1-year period, participants completed two SFFQ and two weighed 7-d dietary records (7DDR). Flavonoid intakes from the SFFQ were estimated separately using Harvard (SFFQHarvard ) and Phenol-Explorer (SFFQPE ) food composition databases. 7DDR flavonoid intakes were derived using the Phenol-Explorer database (7DDRPE ). Validity was assessed using Spearman's rank correlation coefficients deattenuated for random measurement error ( r s ), and reproducibility was assessed using rank intraclass correlation coefficients. Setting: This validation study included primarily participants from two large observational cohort studies. Participants: Six hundred forty-one men and 724 women. Results: When compared with two 7DDRPE, the validity of total flavonoid intake assessed by SFFQPE was high for both men and women ( r s = 0·77 and r s = 0·74, respectively). The r s for flavonoid subclasses ranged from 0·47 for flavones to 0·78 for anthocyanins in men and from 0·46 for flavonols to 0·77 for anthocyanins in women. We observed similarly moderate (0·4–0·7) to high (≥0·7) validity when using SFFQHarvard estimates, except for flavonesHarvard ( r s = 0·25 for men and r s = 0·19 for women). The SFFQ demonstrated high reproducibility for total flavonoid and flavonoid subclass intake estimates when using either food composition database. The intraclass correlation coefficients ranged from 0·69 (flavonolsPE ) to 0·80 (proanthocyanidinsPE ) in men and from 0·67 (flavonolsPE ) to 0·77 (flavan-3-ol monomersHarvard ) in women. Conclusions: SFFQ-derived intakes of total flavonoids and flavonoid subclasses (except for flavones) are valid and reproducible for both men and women.